EFFECT OF THE USE OF MINERAL- VITAMIN COMPLEX RATIONS SLAUGHTER WEIGHT AND CARCASS WEIGHT ON BOAR CROSS BREED AGE 2-6 MONTHS - I P., Juniartha; Siti, N W.; Utami, I. A. P. (Jurnal Peternakan Tropika, 2020)
This study aimed to determine the effect of the use of mineral- vitamin complex in rations to slaughter weight and carcass on boar cross breed the age of 2-6 months. The design used was a randomized block design (RBD) comprising 3 treatments and 4 groups as replication, clustering based on weight. The treatments tested with pollard ration without supplementation of mineral-vitamin complex (A) replacement ration pollard supplemented with rice bran without mineral-vitamin complex (B) pollard replacement ration of rice bran supplemented with mineral-vitamin complex as much as 0.20% (C ). The variables measured were slaughter weight, carcass weight and carcass percentage. The results showed that the replacement of pollard ration rice bran supplemented with mineral-vitamin complex as much as 0, 20% is not significant (P >0.05) can increase slaughter weight, carcass weight and carcass percentage on boar cross breed the age of 2-6 months. It was concluded that supplementation of 0.20% mineral-complex vitamins in the diet can increase the slaughter weight, carcass weight and carcass percentage on boar cross breed. Key words : boar cross breed, carcass, supplementation mineral-vitamin complex